A Study on impact of Consumer Behaviour in Product Acquisition (Trinity Journal of Management, IT & Media (TJMITM), 2022)
In this paper, an effort has been made to convey a general exposition on the behaviour that consumers exhibit while purchasing products and to offer some data on consumer behaviour for citation. The fundamental words that make up the title of this essay, "customer behaviour in product acquisition," are essential since they serve as the foundation for all the pertinent secondary research investigations that were undertaken and summarized in it. The notion of motivation and involvement, knowledge, attitude, perceived risk, risk mitigation technique, and social demographics are all explained in the study.
Keywords: consumer behaviour; Products; Motivation; Attitude; Perceived risk; Risk reduction strategy